RELASI HISTORIS DAN SOSIOKULTURAL ANTARA SUNDA, PRIANGAN, DAN JAWA BARAT: SEBUAH TINJAUAN KRITIS - Mumuh Muhsin Zakaria (Jurnal Kajian Budaya dan Humaniora, 2025)
This article aims to analyze the complex relations between three entities: Sunda, Priangan, and West Java. Many parties often equate the three, whereas each has different contexts, boundaries, and meanings. This research uses a qualitative method with a historical-sociological approach through a literature study. The analysis results show that: (1) Sunda refers to a broader ethnocultural identity, beyond the current borders of West Java Province, characterized by language, belief systems, and customs; (2) Priangan is a colonial Dutch construction formed from Mataram and VOC influences, which shaped an aristocratic identity, “menak” culture, and became the heart of modern Sundanese culture; (3) West Java is a product of the post-independence Indonesian nation-state that froze and administered the diversity within it into one governmental region. The three intersect and form an ongoing dialectic, where West Java is the political container, Priangan is the dominant cultural core, and Sunda is a more inclusive identity umbrella that is sometimes marginalized by the dominance of the Prianganization narrative. Understanding this relationship is crucial for inclusive development policies and the preservation of cultural diversity at the local level. Keywords: Sunda, Priangan, West Java, Identity, History, Sociocultural